An economic perspective on new guidelines on regional aid for 2014-2020 Die neuen Leitlinien für EU-Regionalbeihilfen 2014 bis 2020 aus ökonomischer Sicht - Paha, Johannes (Wirtschaftsdienst, 2013)
This article analyses the European Commission's Guidelines on Regional State Aid for 2014-2020 that were passed in late June 2013. The author argues that some elements of these guidelines are neither in line with economic theory nor with related guidelines and communications of the Commission. Before applying the guidelines, some rules, e.g. on market delineation and foreclosure, should be defined more clearly. © 2013 ZBW and Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-11-17